Multimorbidity increased the risk of urinary incontinence in community-dwelling adults: Results from the English Longitudinal Study On Ageing. (March 2023) - Barbagallo, Mario; Smith, Lee; Koyanagi, Ai; Dominguez, Ligia J.; Fazzari, Anna; Marrone, Eliana; Maggi, Stefania; Ruotolo, Giovanni; Castagna, Alberto; Veronese, Nicola
Highlights: Multimorbidity is highly prevalent in older adults. The association of multimorbidity with urinary incontinence is mainly reported in cross-sectional studies. In the ELSA study, multimorbidity at the baseline is associated with a significant risk of urinary incontinence over 10 years of follow-up. Among the medical conditions examined, only three were significantly associated with incident urinary incontinence, namely asthma, Parkinson's disease, and psychiatric disorder. Abstract: Multimorbidity (MM) is common in older people. Recent evidence, largely from cross-sectional studies, suggests that MM could be a risk factor for urinary incontinence (UI). For this reason, we aimed to explore the association between MM at baseline and incident UI, and which individual chronic medical conditions/factors might explain the association between MM and UI, using data from the English Longitudinal Study on Ageing, during ten years of follow-up. MM was defined as having two or more chronic medical conditions; the presence of UI was assessed using self-reported information. A logistic regression analysis, adjusted for baseline potential confounders, was used to assess the association between MM and UI, reporting the data as odds ratios (ORs) with their 95 % confidence intervals (CIs). Of 9432 initial participants, 6742 (mean age: 64.8 years; 53.2 % females) without UI at baseline were included in the analysis. MM was present at baseline in 48.8 % of the participants. People with MM had a significantly higher cumulative incidence of UI than their counterparts, leading to a significantly higher risk of UI also after adjusting for potential confounders at baseline (OR = 1.30; 95 % CI: 1.14–1.48). Among the medical conditions, only three were significantly associated with incident UI, namely asthma, Parkinson's disease, and psychiatric disorders. In conclusion, MM at baseline was associated with an increased risk of UI during ten years of follow-up, suggesting that UI is more likely to be present in people with several chronic medical conditions.